Nano-graphite asymmetric hollow carbon fibers and methods of making and using same
By using a dense separation layer and a porous support layer of asymmetric hollow carbon fibers in the gas separation membrane, combined with the nanographite structure, the balance problem between selectivity and permeability in the prior art is solved, and the gas separation effect with high selectivity and good permeability is achieved.
Patent Information
- Application Number
- CN202380074206.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-24
- Filing Date
- 2023-10-23
- Publication Date
- 2025-05-30
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When the prior art improves the selectivity of gas separation membranes, it is often accompanied by a decrease in permeability, making it difficult to find a balance between the two.
Asymmetric hollow carbon fiber is used, and its outer wall includes a dense separation layer and a porous support layer. The dense separation layer is composed of a nanographite structure, with a crystal plane spacing of less than 3.6 angstroms and a base surface greater than 1.3 nm, and a micropore radius is greater than 4 angstroms.
It is achieved to improve gas selectivity, especially during the separation of ethylene and ethane without reducing gas permeability.
Smart Images

Figure CN120076859A_ABST
Abstract
Description
[0001] Cross - reference to related applications
[0002] This application claims the benefit of U.S. Provisional Application Serial No. 63 / 418,723, filed on October 24, 2022, the entire disclosure of which is hereby incorporated by reference herein. Technical field
[0003] The embodiments described herein generally relate to gas separation, and more particularly to nano - graphite asymmetric hollow carbon fibers suitable for gas separation. Background art
[0004] Membranes are widely used for the separation of gases and liquids, including, for example, separating acid gases (such as CO 2 and H 2 S) from natural gas, and separating ethylene and ethane from each other. Gas transport through such membranes is typically modeled by an adsorption - diffusion mechanism. Currently, due to their ease of processing and low cost, polymer membranes have been well - studied and widely used for gas separation. However, carbon molecular sieve (CMS) membranes have been shown to have attractive separation performance characteristics that exceed those of polymer membranes.
[0005] The effects of high pyrolysis temperatures (such as greater than 800 °C) have been studied, and although increasing the pyrolysis temperature has been reported to improve selectivity, it is accompanied by a corresponding decrease in permeability at high pyrolysis temperatures. It is desirable to produce asymmetric hollow carbon fibers suitable for CMS membranes that address one or more of the problems presented above, such as improving the selectivity for a selected gas (such as ethylene) while substantially not reducing its permeability. It is also desirable to have such asymmetric hollow carbon fibers that can be incorporated into a CMS membrane having a self - standing hollow asymmetric fiber shape factor. Summary of the invention
[0006] According to aspects, an asymmetric hollow carbon fiber can include an outer wall surrounding a hollow interior space. The outer wall can include a dense separation layer that can have a thickness of from 2 micrometers to 6 micrometers and a porous support layer between the dense separation layer and the hollow interior space. The dense separation layer and the porous support layer can include: a nano - graphite structure having an interplanar spacing of less than 3.6 angstroms; and a basal plane greater than 1.3 nm. The dense separation layer can include micropores having a radius greater than 4 angstroms.
[0007] It should be understood that both the foregoing Summary of the Invention and the following Detailed Description present embodiments of the present technology and are intended to provide an overview or framework for understanding the nature and characteristics of the technology as claimed. Drawings are included to provide a further understanding of the technology, and these drawings are incorporated into and constitute a part of this specification. The drawings illustrate various embodiments and, together with the description, are used to explain the principles and operations of the technology. Additionally, the drawings and description are meant to be illustrative only and are not intended to limit the scope of the claims in any way.
[0008] Additional features and advantages will be set forth in the following Detailed Description, and in part will be obvious to those of ordinary skill in the art from the description or recognized by practicing the embodiments described herein, including the drawings, the following Detailed Description, and the claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Reference will now be made in more detail to various embodiments, some of which are illustrated in the drawings, wherein:
[0010] Figure 1 A cross-section of an asymmetric hollow carbon fiber according to one or more embodiments of the present disclosure is depicted. DETAILED DESCRIPTION
[0011] The asymmetric hollow carbon fibers according to the embodiments disclosed and described herein can advantageously separate olefins from paraffins. Specifically, the asymmetric hollow carbon fibers disclosed herein can advantageously separate ethylene from ethane. Generally, the industrial separation of ethylene from ethane is carried out on a certain scale such that a small improvement in separation performance can have a large impact on the performance of the separation process.
[0012] The embodiments disclosed herein relate to asymmetric hollow carbon fibers. Now referring to Figure 1 , a cross-section of an asymmetric hollow carbon fiber 100 according to an embodiment is shown. The asymmetric hollow carbon fiber 100 can include an outer wall surrounding a hollow inner space 130. The outer wall can include a dense separation layer 110 and a porous support layer 120 between the dense separation layer 110 and the hollow inner space 130. The dense separation layer 110 can have a thickness of about 2 microns to about 6 microns. The dense separation layer 110 and the porous support layer 120 can include: a nano-graphite structure having an interplanar spacing of less than 3.6 angstroms; and a basal plane greater than 1.3 nm. The dense separation layer 110 can include micropores having a radius greater than 4 angstroms. Methods for manufacturing such fibers and for manufacturing carbon molecular sieve membranes containing such fibers are also disclosed in the embodiments. Additionally, methods for using a carbon molecular sieve membrane containing such fibers to separate ethylene from a gas feed containing ethylene and ethane are also disclosed in the embodiments.
[0013] Without being bound by theory, it is believed that the combination of properties of the asymmetric hollow carbon fibers disclosed herein (such as the thickness of the dense separation layer 110, the interplanar spacing dimension, the basal plane dimension, and the micropore size) together correlates with high gas selectivity without an accompanying decrease in gas permeability. It is believed that this combination of properties can act synergistically to provide an improvement in gas selectivity and gas permeability when compared to hollow carbon fibers that do not have the disclosed combination of properties.
[0014] In an embodiment, the hollow carbon fiber can be asymmetric. As used herein, the term "asymmetric" refers to the property of a hollow carbon fiber in which the hollow carbon fiber has at least one relatively dense layer (which can be the dense separation layer 110) and at least one relatively less dense layer (which can be the porous support layer 120). For example, in an embodiment, one layer of the hollow carbon can be greater than or equal to 2 μm and less than or equal to 6 μm and denser than a second layer. The second layer can be thicker than the first layer, such as greater than or equal to 20 μm and less than or equal to 200 μm. In one or more embodiments, the density of the dense separation layer 110 can be greater than the density of the porous support layer 120.
[0015] In one or more embodiments, the dense separation layer 110 can have a thickness of from about 2 microns to about 6 microns. For example, the dense separation layer 110 can have a thickness of from 2 microns to 6 microns, such as from 2 microns to 5 microns, from 2 microns to 4 microns, from 2 microns to 3 microns, from 3 microns to 6 microns, from 3 microns to 5 microns, from 3 microns to 4 microns, from 4 microns to 6 microns, from 4 microns to 5 microns, or from 5 microns to 6 microns. Without being bound by theory, it is believed that when compared to an asymmetric hollow carbon fiber that does not have a dense separation layer 110 having a thickness of from about 2 microns to about 6 microns, the dense separation layer 110 having a thickness of from about 2 microns to about 6 microns (when part of the combination of properties of the asymmetric hollow carbon fibers disclosed herein) can improve the gas selectivity of the fiber.
[0016] In one or more embodiments, the dense separation layer 110 and the porous support layer 120 can comprise a nanographite structure. As used in this disclosure, the term "nanographite" refers to a structure that comprises graphite crystals having dimensions less than 100 nm. In one or more embodiments, the nanographite structure can have an interplanar spacing of less than As used in this disclosure, the term "interplanar spacing" refers to the distance between the planes of carbon atoms that form the graphite crystal. For example, the nanographite structure can have an interplanar spacing of less than less than or even less than The interplanar spacing. In some embodiments, the nanographite structure can have to The interplanar spacing. For example, the nanographite structure may have to to to to to or to The interplanar spacing.
[0017] According to one or more embodiments, the basal plane of the nanographite structure may be greater than 1.3 nm. As used in this disclosure, the term "basal plane" refers to the size of the plane of carbon atoms that form the graphite crystal. For example, the basal plane of the nanographite structure may be greater than 1.5 nm, greater than 5 nm, greater than 10 nm, greater than 20 nm, greater than 30 nm, greater than 40 nm, or even greater than 50 nm. In some embodiments, the basal plane may be less than 100 nm. For example, the basal plane of the nanographite structure may be from 1.3 nm to 100 nm, from 1.3 nm to 75 nm, from 1.3 nm to 50 nm, from 1.3 nm to 40 nm, from 1.3 nm to 30 nm, from 1.3 nm to 20 nm, from 1.3 nm to 10 nm, from 1.3 nm to 5 nm, from 1.3 nm to 1.5 nm, from 1.5 nm to 100 nm, from 1.5 nm to 75 nm, from 1.5 nm to 50 nm, from 1.5 nm to 40 nm, from 1.5 nm to 30 nm, from 1.5 nm to 20 nm, from 1.5 nm to 10 nm, from 1.5 nm to 5 nm, from 5 nm to 100 nm, from 5 nm to 75 nm, from 5 nm to 50 nm, from 5 nm to 40 nm, from 5 nm to 30 nm, from 5 nm to 20 nm, from 5 nm to 10 nm, from 10 nm to 100 nm, from 10 nm to 75 nm, from 10 nm to 50 nm, from 10 nm to 40 nm, from 10 nm to 30 nm, from 10 nm to 20 nm, from 20 nm to 100 nm, from 20 nm to 75 nm, from 20 nm to 50 nm, from 20 nm to 40 nm, from 20 nm to 30 nm, from 30 nm to 100 nm, from 30 nm to 75 nm, from 30 nm to 50 nm, from 30 nm to 40 nm, from 40 nm to 100 nm, from 40 nm to 75 nm, from 40 nm to 50 nm, from 50 nm to 100 nm, from 50 nm to 75 nm, or from 75 nm to 100 nm.
[0018] Without being bound by theory, it is believed that a nanographite structure having a basal plane greater than 1.3 nm and an interplanar spacing less than may be associated with an asymmetric hollow carbon fiber that has improved gas selectivity and gas permeability when compared to an asymmetric hollow carbon fiber that does not have such a nanographite structure.
[0019] As disclosed herein, in one or more embodiments, the dense separation layer 110 may include micropores. In one or more embodiments, the micropores may have a radius greater than , as determined by small angle X-ray scattering. For example, the micropores may have a radius greater than greater than greater than greater than greater than greater than greater than greater than greater than or even greater than . In one or more embodiments, the micropores may have a radius less than , as determined by small angle X-ray scattering. For example, the micropores may have to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to to or to The radius. Without being bound by theory, it is believed that when compared to an asymmetric hollow fiber that does not contain micropores with a radius greater than an asymmetric hollow carbon fiber with a dense separation layer 110 that contains micropores with a radius greater than as determined by a small angle can improve the gas selectivity of the asymmetric hollow carbon fiber.
[0020] In one or more embodiments, the asymmetric hollow carbon fiber may have a nanocrystalline graphite structure. As used in the present disclosure, the term "nanocrystalline graphite" refers to a fiber that has been transformed from an amorphous or non-crystalline carbon structure to a crystalline graphite structure. The transformation from amorphous carbon to crystalline graphite can be determined using Raman spectroscopy. Raman spectroscopy uses light to measure molecular vibrations, and these vibrations can be used to determine characteristics (such as molecular structure and crystallinity). Without being bound by theory, it is believed that when the carbon fiber transforms from an amorphous structure to a nanocrystalline structure, the intensity ratio of the Raman D peak to the Raman G peak initially increases and then decreases. It is believed that this "flip" of the intensity ratio can be used to determine whether the asymmetric hollow carbon fiber 100 has been transformed from an amorphous carbon structure to a nanocrystalline graphite structure.
[0021] In one or more embodiments, the asymmetric hollow carbon fiber 100 may include pyrrole-based nitrogen in an amount less than 50% of the total amount of nitrogen in the fiber. For example, the asymmetric hollow carbon fiber 100 may include pyrrole-based nitrogen in an amount less than 45% of the total amount of nitrogen in the fiber, such as pyrrole-based nitrogen in an amount less than 40%, less than 35%, less than 30%, less than 25%, less than 20%, less than 15%, or even less than 10% of the total amount of nitrogen in the fiber. Without being bound by theory, it is believed that a pyrrole-based nitrogen percentage of less than 50% of the total amount of nitrogen in the fiber may indicate that the fiber has been formed via pyrolysis at a high temperature as compared to a fiber having a pyrrole-based nitrogen percentage greater than 50% of the total amount of nitrogen in the fiber.
[0022] In one or more embodiments, the dense separation layer 110 of the asymmetric hollow carbon fiber 100 may include oxygen in an amount greater than 5 atomic % of the total amount of atoms of the dense separation layer 110. In one or more embodiments, the dense separation layer 110 of the asymmetric hollow carbon fiber 100 may include oxygen in an amount less than 15 atomic % of the total amount of atoms of the dense separation layer 110. For example, the asymmetric hollow carbon fiber 100 may include oxygen in an amount of 5 atomic % to 15 atomic % of the total atoms of the dense separation layer 110, such as 5 atomic % to 12.5 atomic %, 5 atomic % to 10 atomic %, 5 atomic % to 7.5 atomic %, 7.5 atomic % to 15 atomic %, 7.5 atomic % to 12.5 atomic %, 7.5 atomic % to 10 atomic %, 10 atomic % to 15 atomic %, 10 atomic % to 12.5 atomic %, or 12.5 atomic % to 15 atomic %. Without being bound by theory, it is believed that an oxygen content of 5 atomic % to 15 atomic % of the total atoms of the dense separation layer may be associated with improved gas permeability and selectivity of the fiber when compared to a fiber having an oxygen content of less than 5 atomic % or greater than 15 atomic %.
[0023] In one or more embodiments, the asymmetric hollow carbon fiber 100 may have a D(002) peak in transmission that is less than as measured by X-ray scattering at an energy level of 17 keV. For example, the asymmetric hollow carbon fiber 100 may have a D(002) peak that is less than less than less than less than or even less than In some embodiments, the D(002) peak in transmission may be at least For example, the asymmetric hollow carbon fiber 100 may have to to to to to to to to to to to to to to to to to to to to to to to to to to to or to The D(002) peak. Without being bound by theory, it is believed that less than as measured by X-ray scattering at an energy level of 17 keV indicates that most of the fiber has carbonized to form the asymmetric hollow carbon fiber 100.
[0024] In one or more embodiments, multiple asymmetric hollow carbon fibers are combined to form a carbon molecular sieve membrane. In an embodiment, the carbon molecular sieve membrane may include channels formed between the dense separation layers 110 of adjacent fibers. In an embodiment, the carbon molecular sieve membrane may not include an external support.
[0025] In an embodiment, the asymmetric membrane may be a solid composed of an extremely thin, dense skin on a thick porous substructure, and the thick porous substructure may be the same or different material from the dense surface layer. In an embodiment, the asymmetric membrane may be fabricated in a single step by phase inversion, or a thin layer may be coated on a pre-prepared porous support using dip coating. These layers in the asymmetric membrane may be produced by physically coating or by chemical modification. The asymmetric membrane may be in the form of a hollow fiber configuration. In an embodiment, the asymmetric membrane may optionally include a third layer of the same or different material to enhance membrane performance.
[0026] In one or more embodiments, a method of manufacturing the asymmetric hollow carbon fiber 100 may include providing a polymer precursor fiber. The polymer precursor fiber may be provided by forming a precursor polymer into a hollow fiber using conventional methods. For example, a coextrusion process including processes such as a dry-jet wet spinning process (where there is an air gap between the tip of the spinneret and the coagulation or quench bath) or a wet spinning process (with a zero air gap distance) may be used to form the polymer precursor fiber.
[0027] The polymer precursor fiber can be any available polymer for manufacturing asymmetric hollow carbon fibers. In some embodiments, the polymer precursor fiber can be a polyimide. The polyimide can be a conventional or fluorinated polyimide. In some embodiments, the polyimide used to form the polymer precursor fiber can comprise at least two different moieties selected from the following: 2,4,6-trimethyl-1,3-phenylenediamine (DAM), diaminodiphenyl ether (ODA), dimethyl-3,7-diaminodiphenyl-thiophene-5,5'-dioxide (DDBT), 3,5-diaminobenzoic acid (DABA), 2,3,5,6-tetramethyl-1,4-phenylenediamine (durene), m-phenylenediamine (m-PDA), 2,4-diaminotoluene (2,4-DAT), tetramethylmethylenedianiline (TMMDA), 4,4'-diamino-2,2'-biphenyldisulfonic acid (BDSA); 5,5'-[2,2,2-trifluoro-1-(trifluoromethyl)ethylidene]-1,3-isobenzofurandione (6FDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), pyromellitic dianhydride (PMDA), 4,4'-oxybisphthalic anhydride (ODPA), 1,4,5,8-naphthalenetetracarboxylic dianhydride (NTDA), and benzophenonetetracarboxylic dianhydride (BTDA). In some embodiments, the two different moieties are two or more of 6FDA, BPDA, and DAM.
[0028] In one or more embodiments, the polyimide polymer precursor can be 6FDA / BPDA-DAM. 6FDA / BPDA-DAM can be synthesized from a combination of three monomers, DAM, 6FDA, and BPDA, via a thermal or chemical method, and each of these monomers can be commercially available, for example, from Sigma-Aldrich Corporation. The following Formula 1 shows a representative structure of 6FDA / BPDA-DAM with the potential to adjust the ratio between X and Y to regulate polymer properties. As used in the following examples, a 1:1 ratio of component X to component Y can also be abbreviated as 6FDA / BPDA(1:1)-DAM.
[0029]
[0030] In one or more embodiments, the polyimide polymer precursor can be 6FDA-DAM. 6FDA-DAM does not contain BPDA, such that Y equals zero in Formula 1 above. The following Formula 2 shows a representative structure of this polyimide.
[0031]
[0032] In one or more embodiments, the polyimide polymer precursor can be MATRIMID TM5218 (Huntsman Advanced Materials), a commercially available polyimide that is a copolymer of 3,3',4,4'-benzophenone tetracarboxylic dianhydride and 5(6)-amino-1-(4'-aminophenyl)-1,3,3-trimethylindane (BTDA-DAPI).
[0033] In one or more embodiments, the polyimide polymer precursor can be 6FDA / PMDA-DAM as shown in Formula 3 below.
[0034]
[0035] In one or more embodiments, the polymer precursor hollow fibers are substantially defect-free. As used in this disclosure, the term "defect-free" means that the selectivity of a gas pair (usually oxygen (O 2 )) and nitrogen (N 2 )) through the polymer precursor hollow fiber membrane is at least 90% of the selectivity of the same gas pair through a dense membrane made of the same composition used to make the polymer precursor hollow fiber membrane. For example, the 6FDA / BPDA(1:1)-DAM polymer has an inherent O 2 / N 2 selectivity (also referred to as "dense membrane selectivity").
[0036] One way to produce asymmetric hollow carbon fibers according to the embodiments disclosed and described herein and to use the asymmetric hollow carbon fibers for CMS membranes is by pyrolyzing the polymer hollow fibers at a temperature greater than 900 degrees Celsius (°C). It is common knowledge that increasing the pyrolysis temperature results in a corresponding increase in selectivity, but increasing the pyrolysis temperature results in a decrease in permeability. For example, Koros et al. (Adv. Mater. 2017, 29, 1701631) reported the synthesis of a hyper-selective CMS dense membrane by pyrolyzing a MATRIMID-based precursor at a high temperature (900 °C). This trend is consistent with Pinnau et al. (https: / / doi.org / 10.1016 / j.memsci.2019.05.020), who reported that the membrane permeability decreases with an increase in the membrane selectivity of the selected gas pair. Thus, it is common knowledge that permeability and ultra-high selectivity are inversely correlated. Additionally, the membranes formed using these conditions typically only exhibit a dense membrane shape factor.
[0037] However, unexpected anomalies in the above trends are observed (i.e., the inverse relationship between permeability and selectivity), where a moderate increase in permeability with a step change in selectivity is observed for fibers pyrolyzed at certain temperatures. When forming a CMS membrane under certain pyrolysis conditions, this allows for the synthesis of highly selective CMS asymmetric membranes without sacrificing too much permeability. Fibers pyrolyzed using these conditions have been found to have the physical properties as described above. Thus, while the methods described herein can be used to produce the asymmetric hollow carbon fibers of the present disclosure, it is expected that other methods can be used to produce asymmetric hollow carbon fibers having the properties described herein.
[0038] The pyrolysis conditions will now be described. Any suitable means for supporting the hollow fiber CMS membrane during pyrolysis can be used, including sandwiching between two wire meshes or using a stainless steel mesh plate in combination with stainless steel wires, and as described in U.S. Patent No. 8,709,133, column 6, lines 58 to column 7, line 4, which is incorporated by reference.
[0039] The precursor polymer can be pyrolyzed under various inert gas purges or vacuum conditions (e.g., a pressure less than or equal to 0.1 mbar) to form a hollow fiber CMS membrane (i.e., carbonize the precursor polymer). U.S. Patent No. 6,565,631 describes a heating method for pyrolyzing polymeric fibers to form a hollow fiber CMS membrane, and this U.S. patent is incorporated herein by reference. According to an embodiment, the pyrolysis temperature of the method for manufacturing a hollow fiber carbon membrane can be greater than or equal to 900 °C and less than or equal to 1200 °C. The pyrolysis temperature can be adjusted in combination with the pyrolysis atmosphere to adjust the performance characteristics of the resulting hollow fiber CMS membrane. In an embodiment, the pyrolysis temperature can be greater than or equal to 925 °C and less than or equal to 1200 °C, greater than or equal to 950 °C and less than or equal to 1200 °C, greater than or equal to 975 °C and less than or equal to 1200 °C, greater than or equal to 1000 °C and less than or equal to 1200 °C, greater than or equal to 1025 °C and less than or equal to 1200 °C, greater than or equal to 1050 °C and less than or equal to 1200 °C, greater than or equal to 1075 °C and less than or equal to 1200 °C, greater than or equal to 1100 °C and less than or equal to 1200 °C, greater than or equal to 1125 °C and less than or equal to 1200 °C, greater than or equal to 1150 °C and less than or equal to 1200 °C, greater than or equal to 1175 °C and less than or equal to 1200 °C, greater than or equal to 900 °C and less than or equal to 1175 °C, greater than or equal to 925 °C and less than or equal to 1175 °C, greater than or equal to 950 °C and less than or equal to 1175 °C, greater than or equal to 975 °C and less than or equal to 1175 °C, greater than or equal to 1000 °C and less than or equal to 1175 °C, greater than or equal to 1025 °C and less than or equal to 1175 °C, greater than or equal to 1050 °C and less than or equal to 1175 °C, greater than or equal to 1075 °C and less than or equal to 1175 °C, greater than or equal to 1100 °C and less than or equal to 1175 °C, greater than or equal to 1125 °C and less than or equal to 1175 °C, greater than or equal to 1150 °C and less than or equal to 1175 °C, greater than or equal to 900 °C and less than or equal to 1150 °C, greater than or equal to 925 °C and less than or equal to 1150 °C, greater than or equal to 950 °C and less than or equal to 1150 °C, greater than or equal to 975 °C and less than or equal to 1150 °C, greater than or equal to 1000 °C and less than or equal to 1150 °C, greater than or equal to 1025 °C and less than or equal to 1150 °C, greater than or equal to 1050 °C and less than or equal to 1150 °C, greater than or equal to 1075 °C and less than or equal to 1150 °C, greater than or equal to 1100 °C and less than or equal to 1150 °C, greater than or equal to 1125 °C and less than or equal to 1150 °C, greater than or equal to 900 °C and less than or equal to 1125 °C, greater than or equal to 925 °C and less than or equal to 1125 °C, greater than or equal to 950 °C and less than or equal to 1125 °C, greater than or equal to 975 °C and less than or equal to 1125 °C,Greater than or equal to 1000 °C and less than or equal to 1125 °C, greater than or equal to 1025 °C and less than or equal to 1125 °C, greater than or equal to 1050 °C and less than or equal to 1125 °C, greater than or equal to 1075 °C and less than or equal to 1125 °C, greater than or equal to 1100 °C and less than or equal to 1125 °C, greater than or equal to 900 °C and less than or equal to 1100 °C, greater than or equal to 925 °C and less than or equal to 1100 °C, greater than or equal to 950 °C and less than or equal to 1100 °C, greater than or equal to 975 °C and less than or equal to 1100 °C, greater than or equal to 1000 °C and less than or equal to 1100 °C, greater than or equal to 1025 °C and less than or equal to 1100 °C, greater than or equal to 1050 °C and less than or equal to 1100 °C, greater than or equal to 1075 °C and less than or equal to 1100 °C, greater than or equal to 900 °C and less than or equal to 1075 °C, greater than or equal to 925 °C and less than or equal to 1075 °C, greater than or equal to 950 °C and less than or equal to 1075 °C, greater than or equal to 975 °C and less than or equal to 1075 °C, greater than or equal to 1000 °C and less than or equal to 1075 °C, greater than or equal to 1025 °C and less than or equal to 1075 °C, greater than or equal to 1050 °C and less than or equal to 1075 °C, greater than or equal to 900 °C and less than or equal to 1050 °C, greater than or equal to 925 °C and less than or equal to 1050 °C, greater than or equal to 950 °C and less than or equal to 1050 °C, greater than or equal to 975 °C and less than or equal to 1050 °C, greater than or equal to 1000 °C and less than or equal to 1050 °C, greater than or equal to 1025 °C and less than or equal to 1050 °C, greater than or equal to 900 °C and less than or equal to 1025 °C, greater than or equal to 925 °C and less than or equal to 1025 °C, greater than or equal to 950 °C and less than or equal to 1025 °C, greater than or equal to 975 °C and less than or equal to 1025 °C, greater than or equal to 1000 °C and less than or equal to 1025 °C, greater than or equal to 900 °C and less than or equal to 1000 °C, greater than or equal to 925 °C and less than or equal to 1000 °C, greater than or equal to 950 °C and less than or equal to 1000 °C, greater than or equal to 975 °C and less than or equal to 1000 °C, greater than or equal to 900 °C and less than or equal to 975 °C, greater than or equal to 925 °C and less than or equal to 975 °C, greater than or equal to 950 °C and less than or equal to 975 °C, greater than or equal to 900 °C and less than or equal to 950 °C,Greater than or equal to 925 °C and less than or equal to 950 °C or greater than or equal to 900 °C and less than or equal to 925 °C. At pyrolysis temperatures below 900 °C, the desired selectivity may not be obtained, and at temperatures above 1200 °C, the structure of the CMS membrane may be damaged. It is contemplated that an acceptable range of pyrolysis temperatures can be greater than or equal to any of the temperatures described herein and less than or equal to any of the temperatures described herein. Without being bound by theory, it is believed that pyrolysis temperatures above 900 °C can form asymmetric hollow carbon fibers that transform from an amorphous carbon structure to a nanocrystalline graphite structure.
[0040] The pyrolysis soak time (i.e., the duration at the pyrolysis temperature) can vary (and the soak time may not be included), but can be, for example, greater than or equal to 1 hour and less than or equal to 24 hours, greater than or equal to 2 hours and less than or equal to 8 hours, greater than or equal to 4 hours and less than or equal to 6 hours. Exemplary heating profiles can include: (1) starting at a first set point of about 50 °C; (2) heating to a second set point of about 250 °C at a rate of about 13.3 °C per minute; (3) heating to a third set point of about 535 °C at a rate of about 3.85 °C per minute; (4) heating to a fourth set point of about 550 °C at a rate of about 0.25 °C per minute. The fourth set point can then be maintained for the determined soak time.
[0041] The precursor polymer can be carbonized under different inert gas purge or vacuum conditions, preferably under inert gas purge conditions for vacuum pyrolysis, preferably at low pressure (e.g., less than 0.1 mbar). In an embodiment, the pyrolysis utilizes a controlled inert purge gas atmosphere with a small amount of an oxidant such as oxygen. Thus, in one or more embodiments, the pyrolysis atmosphere contains an inert gas and oxygen. In an embodiment, the inert gas is selected from the group consisting of nitrogen, helium, argon, or combinations thereof. In one or more embodiments, the inert purge gas is argon, and thus in an embodiment, the pyrolysis atmosphere contains argon and oxygen. It has been found that by pyrolyzing in trace oxygen in an inert gas mixture, the permeability of membranes pyrolyzed at high temperatures (e.g., greater than or equal to 900 °C) can be further increased. In contrast, conventional knowledge holds that the presence of oxygen reduces the permeability of membranes pyrolyzed at 550 °C or higher temperatures (see U.S. Patent Application Publication No. 2013 / 030592).
[0042] In one or more embodiments, the purge gas atmosphere can contain an amount of oxygen less than 40 ppm. In some embodiments, the purge gas atmosphere can contain an amount of oxygen less than 10 ppm. In an embodiment, the purge gas atmosphere can contain at least 5 ppm of oxygen. For example, the purge gas atmosphere can contain from 5 ppm to 40 ppm, from 5 ppm to 35 ppm, from 5 ppm to 30 ppm, from 5 ppm to 25 ppm, from 5 ppm to 20 ppm, from 5 ppm to 15 ppm, from 5 ppm to 10 ppm, from 10 ppm to 40 ppm, from 10 ppm to 35 ppm, from 10 ppm to 30 ppm, from 10 ppm to 25 ppm, from 10 ppm to 20 ppm, from 10 ppm to 15 ppm, from 15 ppm to 40 ppm, from 15 ppm to 35 ppm, from 15 ppm to 30 ppm, from 15 ppm to 25 ppm, from 15 ppm to 20 ppm, from 20 ppm to 40 ppm, from 20 ppm to 35 ppm, from 20 ppm to 30 ppm, from 20 ppm to 25 ppm, from 25 ppm to 40 ppm, from 25 ppm to 35 ppm, from 25 ppm to 30 ppm, from 30 ppm to 40 ppm, from 30 ppm to 35 ppm, or from 35 ppm to 40 ppm of oxygen.
[0043] After pyrolysis, the formed hollow fiber CMS membrane is cooled to a temperature close to room temperature, such as less than or equal to 50 °C. The cooling can occur at any useful rate, such as passive cooling (e.g., turning off the power to the furnace and allowing natural cooling). Alternatively, more rapid cooling may be required, such as by using known techniques to achieve more rapid cooling. Known techniques include but are not limited to cooling fans or using a water-cooled jacket or leaving the furnace open to the surrounding environment.
[0044] In one or more embodiments, a plurality of asymmetric hollow carbon fibers are combined to form a carbon molecular sieve membrane. In some embodiments, the carbon molecular sieve membrane can include channels formed between the dense separation layers 110 of adjacent fibers. In some embodiments, the carbon molecular sieve membrane can not include an external support. In some embodiments, the carbon molecular sieve membrane can be formed by pyrolyzing a plurality of polymer precursor fibers, as described above.
[0045] In one or more embodiments, a method for separating ethylene from a gas feed comprising ethylene and ethane includes: providing a CMS membrane comprising the asymmetric hollow carbon fibers as described herein; and flowing the gas feed through a channel of the CMS membrane to produce a first stream having an increased concentration of ethylene and a second stream having an increased concentration of ethane. In some embodiments, the CMS membrane is desirably formed into a module including a sealable enclosure composed of a plurality of carbon molecular sieve membranes, the plurality of carbon molecular sieve membranes being composed of at least one carbon molecular sieve membrane comprising the asymmetric hollow carbon fibers of the present disclosure, the carbon molecular sieve membrane being contained within the sealable enclosure. The sealable enclosure has: an inlet for introducing a gas feed composed of at least two different gas molecules; a first outlet for allowing the permeate gas stream to exit; and a second outlet for allowing the retentate gas stream to exit.
[0046] According to one aspect, alone or in combination with any other aspect, the asymmetric hollow carbon fiber includes an outer wall surrounding a hollow interior space. The outer wall includes a dense separation layer having a thickness of 2 to 6 microns and a porous support layer between the dense separation layer and the hollow interior space. The dense separation layer and the porous support layer include: a nano-graphite structure having an interplanar spacing of less than 3.6 angstroms; and a basal plane greater than 1.3 nm. The dense separation layer includes micropores having a radius greater than 4 angstroms.
[0047] A second aspect of the present disclosure includes any of the foregoing aspects or combinations of aspects, wherein the asymmetric hollow carbon fiber has a nano-crystalline graphite structure.
[0048] A third aspect of the present disclosure includes any of the foregoing aspects or combinations of aspects, wherein the fiber contains pyrrole-based nitrogen in an amount less than 50% of the total amount of nitrogen in the fiber.
[0049] A fourth aspect of the present disclosure includes any of the foregoing aspects or combinations of aspects, wherein the dense separation layer contains oxygen in an amount greater than 5 atomic % of the total atoms of the dense separation layer.
[0050] A fifth aspect of the present disclosure includes any of the foregoing aspects or combinations of aspects, wherein the dense separation layer contains oxygen in an amount less than 15 atomic % of the total atoms of the dense separation layer.
[0051] A sixth aspect of the present disclosure includes any of the foregoing aspects or combinations of aspects, wherein the fiber contains oxygen in an amount less than 5 atomic % of the total atoms of the fiber.
[0052] A seventh aspect of the present disclosure includes any of the foregoing aspects or combinations of aspects, wherein the fiber has a D(002) peak of less than 4.0 A in transmission, as measured by X-ray scattering at an energy level of 17 keV.
[0053] The eighth aspect of the present disclosure includes any of the foregoing aspects or combinations of aspects, wherein the carbon molecular sieve membrane comprises a plurality of asymmetric hollow carbon fibers of any of the foregoing aspects, and the carbon molecular sieve membrane includes channels formed between the dense separation layers of adjacent fibers.
[0054] The ninth aspect of the present disclosure includes any of the foregoing aspects or combinations of aspects, wherein the carbon membrane does not include an external support.
[0055] The tenth aspect of the present disclosure includes a method for separating ethylene from a gas feed comprising ethylene and ethane, the method comprising: providing a carbon molecular sieve membrane of the eighth aspect or the ninth aspect; and flowing the gas feed through the channels of the carbon molecular sieve membrane to produce a first stream having an increased concentration of ethylene and a second stream having an increased concentration of ethane.
[0056] The eleventh aspect includes a method for manufacturing the asymmetric hollow carbon fibers of the first aspect to the seventh aspect, the method comprising: preparing a polymer precursor fiber; and pyrolyzing the polymer precursor fiber in a low-oxygen atmosphere at a temperature greater than 900 °C to form the asymmetric hollow carbon fiber.
[0057] The twelfth aspect of the present disclosure includes any of the foregoing aspects or combinations of aspects, wherein the pyrolysis of the polymer precursor occurs in an atmosphere comprising an inert gas and oxygen.
[0058] The thirteenth aspect of the present disclosure includes any of the foregoing aspects or combinations of aspects, wherein the atmosphere comprises less than 40 ppm of oxygen.
[0059] The fourteenth aspect of the present disclosure includes any of the foregoing aspects or combinations of aspects, wherein the atmosphere comprises less than 10 ppm of oxygen.
[0060] The fifteenth aspect of the present disclosure includes any of the foregoing aspects or combinations of aspects, wherein the precursor polymer is a polyimide.
[0061] Testing method
[0062] Gas permeability and selectivity
[0063] The gas permeation characteristics of the membrane can be determined by gas permeation experiments. Two intrinsic properties are used to evaluate the separation performance of the membrane material: its "permeability" (a measure of the inherent productivity of the membrane); and its "selectivity" (a measure of the membrane separation efficiency). The "permeability" is typically determined in units of Barrer (1 Barrer = 10 -10 [cm 3 (STP) cm] / [cm 2 s cmHg]), which is calculated by dividing the flux (n i ) by the partial pressure difference (Δp i) and is calculated by multiplying by the membrane thickness (l).
[0064]
[0065] Another term, "permeance", is defined herein as the productivity of an asymmetric hollow fiber membrane and is typically measured in gas permeation units (GPU) (1 GPU = 10 -6 [cm 3 (STP)] / [cm 2 s cmHg]) and is determined by dividing the permeability by the effective membrane separation layer thickness.
[0066]
[0067] Finally, "selectivity" is defined herein as the ability of one gas to permeate through the membrane or the permeance of the same property relative to another gas. It is measured as a unitless ratio.
[0068]
[0069] Raman spectroscopy
[0070] Raman spectroscopy was performed on the carbon molecular sieve hollow carbon fibers in a side-on-side geometry with a 180-degree backscattering geometry using a Thermo Scientific Almega DXR MicroRaman spectrometer. A 20x microscope objective with 0.3 NA was used with a 532 nm excitation source. A CCD detector was used to collect data. The MicroRaman system was interfaced with a computer system that controlled both the high-resolution grating (approx. 4 cm -1 resolution) and the laser power (via a neutral density filter through the OMNIC software package). Raman spectra were plotted and peak fitting was performed using a macro built within the IgorPro software package. Two peaks with a Lorentzian shape were used to fit the D and G peaks. A linear background was used and the linear background was fit between 800 and 2200 cm -1 between.
[0071] X-ray scattering
[0072] X-ray scattering was performed at beamline 5-ID-D of the Dupont-Northwestern-Dow Collaborative Access Team (DND-CAT), which is part of the Advanced Photon Source at Argonne National Lab. The X-ray energy was set to Small-angle and wide-angle X-ray scattering of previously carbonized fibers was measured at the same beamline in air using transmission geometry. The wide-angle X-ray scattering was plotted and analyzed with JADE, while the SAXS values were plotted and analyzed with the IRENA SAS macro within IgorPro. The Rg was calculated using a unified fitting algorithm, while the crystallite size was calculated using the Scherrer formula.
[0073] Scanning electron microscopy
[0074] Scanning electron microscopy (SEM) was performed using a Hitachi SU-70FE-SEM with a secondary electron detector. An acceleration voltage of 3 kV and an emission current of 16,000 nA were used to collect images in the field-free mode. Samples were prepared by breaking the fibers while immersed in a pentane solvent. The use of the pentane solvent allowed for complete breakage of the fibers. Final polishing was not performed on the cross-section before mounting them onto aluminum stubs with carbon tape.
[0075] X-ray photoelectron spectroscopy
[0076] XPS spectra were obtained by irradiating the fibers with X-rays while measuring the binding energy and current of photoelectrons escaping from the top 0 nm to 10 nm of the fibers. All elements have unique binding energies, and the elemental peak areas were used to determine the surface composition. XPS is sensitive to all elements except hydrogen and helium. The resulting surface composition was forced to 100%. XPS spectra were obtained using a Thermo K-Alpha XPS. The X-ray source was monochromatic Al Kα at 72 watts (12 kV, 6 mA). The analyzer pass energies were 200 eV (survey: 50 ms, 1 eV / step, 5 scans), 80 eV (quantitative scan: 50 ms, 0.15 eV / step, 5 scans), and 20 eV (high-resolution C and N scans: 50 ms, 0.10 eV / step, 15 scans). The takeoff angle was 90°. Depending on the fiber diameter, the analysis area diameter of the fiber was 100 μm or 50 μm. The analysis area diameter of the ground sample was 400 μm. An immersion electron gun was not required except for cryo-annealed samples that required a standard immersion electron gun setting. Data was processed using Thermo Avantage software with Thermo-modified XPS sensitivity factors. Data was collected from 5 data points along the fiber or across the ground powder.
[0077] Example
[0078] The various embodiments of the present disclosure will be further illustrated by the following examples. The examples are illustrative in nature and should not be construed as limiting the subject matter of the present disclosure.
[0079] CMS membrane preparation
[0080] The CMS membrane is fabricated using 6FDA-BPDA-DAM polymer. 6FDA-BPDA-DAM is obtained from Akron Polymer Systems, Akron, OH. The polymer is dried under vacuum at 110 °C for 24 hours and then a dope solution is formed. The dope solution is prepared by mixing the 6FDA-BPDA-DAM polymer with the solvents and compounds in Table 1 and performing roll mixing for a period of about 3 weeks at a roll speed of 5 revolutions per minute (rpm) in a Qorpak TM glass bottle capped with Teflon TM to form a homogeneous dope solution.
[0081] Table 1 - Stock solution formulation
[0082]
[0083] NMP = N-methyl-2-pyrrolidone; THF = tetrahydrofuran
[0084] The homogeneous dope solution is loaded into a 500 milliliter (mL) syringe pump and degassed overnight by heating the pump to a set point temperature of 50 °C to 60 °C using a heating tape.
[0085] The core liquid (85 wt% NMP and 15 wt% water based on the total core liquid weight) is loaded into a separate 100 mL syringe pump and then the dope solution and the core liquid are co-extruded through a spinneret operating at a flow rate of 180 milliliters per hour (mL / hr) for the dope solution; 60 mL / hr for the core liquid. Both the core liquid and the dope solution in the pipeline between the transfer pump and the spinneret are filtered using 40 μm and 2 μm metal filters. The temperature is controlled at a set point temperature of 70 °C using thermocouples and heating tapes placed on the spinneret, the dope filter, and the dope pump.
[0086] After passing through a fifteen centimeter (cm) air gap, the nascent fibers formed by the spinneret are quenched in a water bath (50 °C) and phase separation of the fibers occurs. The fibers are collected using a 0.32 meter (m) diameter polyethylene roller through Teflon guides and operated at a take-up rate of 30 meters per minute (m / min).
[0087] The fibers are cut from the roller and rinsed at least four times in a separate water bath over a 48-hour period. The fibers are rinsed in a glass container and solvent exchanged three times with methanol for 20 minutes each, and then exchanged with hexane for 20 minutes, and then the fibers are recovered and dried under vacuum at a set point temperature of 110 °C for one hour, or dried under vacuum at 75 °C for 3 hours.
[0088] Prior to pyrolyzing the fibers, the above fibers (also referred to as "precursor fibers") of the sample amount are tested for epidermal integrity. One or more hollow precursor fibers are filled into a 1 / 4 inch (0.64 cm) (outer diameter, OD) stainless steel pipe. Each pipe end is connected to a 1 / 4 inch (0.64 cm) stainless steel tee; and each tee is connected to a 1 / 4 inch (0.64 cm) male and female NPT pipe fitting, which is sealed to the NPT connector with epoxy resin. The pure gas permeability test is performed in a constant pressure system maintained at 35 °C. For each permeability test, the entire system and the leak rate are determined to ensure that the leak is less than 1% of the slowest gas permeability rate. After evacuation, the upstream end of the pipe (the end closest to the feed source) is pressurized with the feed gas (e.g., pure oxygen or pure nitrogen), while keeping the downstream end (the end farthest from the feed source) under vacuum. The pressure rise in the constant, known downstream volume over time is recorded using LABVIEW software (National Instruments, Austin, TX, USA) until a steady state is reached. The permeability of each gas through the membrane is determined by the pressure rise rate, the membrane area, and the pressure difference across the membrane. The selectivity of each gas pair is calculated in the form of the ratio of the individual gas permeabilities.
[0089] The precursor fibers are pyrolyzed in a pyrolysis chamber that has an oxygen content maintained between 5 ppm and 10 ppm at room temperature (using Ar as an inert purge gas), while for Sample 3, the oxygen content is raised to 30 ppm by introducing a premix of 30 ppm oxygen and Ar. After pyrolyzing the membranes, single fiber modules are fabricated and tested for C2H4 / C2H6 gas pair permeability. The pyrolyzed and / or oxidized CMS hollow fibers are encapsulated in a stainless steel housing to test gas separation performance. The membrane module is placed in an oven with temperature control (Quincy Lab, Inc., Chicago, IL). The test gas flow rate is controlled by a mass flow controller (Brooks Instrument, Hatfield, PA), and the pressure is monitored and controlled by a pressure sensor. In these experiments, the single fiber CMS fiber module is maintained at a constant upstream pressure at 35 °C. Argon is used as a purge gas to transport the permeate to the downstream flow meter and gas chromatograph (GC). The composition of the permeate and purge mixture is measured using a Maxum II Process GC (Siemens, Munich, Germany), and the permeate flow rate is measured using a Mesalabs Bios Drycal flow meter (Mesa Labs, Inc., Butler, NJ). The volumetric flow rate from the Bios DryCal flow meter and the composition from the GC are used to analyze the permeability and selectivity of the fibers in the test gas system.
[0090] Table 2
[0091]
[0092]
[0093] Table 2 shows an initial decrease in ethylene permeability as the pyrolysis temperature is increased up to 800 °C (see, for example, Comparative Examples A to C). However, at pyrolysis temperatures greater than 800 °C, the permeability of ethylene also increases corresponding to a sharp increase in the selectivity of the ethylene / ethane gas pair (see, for example, Samples 1 to 3). This increase in both permeability and selectivity corresponds to a transition from an amorphous carbon state (Am) to a nanocrystalline graphite structure (Nc), as indicated by the "flip" in the I(D) / I(G) ratio from Comparative Example C to Samples 1 to 3.
[0094] It will be apparent to those skilled in the art that various modifications can be made to the described embodiments without departing from the spirit and scope of the claimed subject matter. Accordingly, this specification is intended to cover modifications and variations of the described embodiments, provided such modifications and variations fall within the scope of the appended claims and their equivalents.
Claims
1. An asymmetric hollow carbon fiber, the asymmetric hollow carbon fiber comprising an outer wall surrounding a hollow interior space, wherein the outer wall comprises a dense separation layer having a thickness of 2 to 6 microns and a porous support layer between the dense separation layer and the hollow interior space, the dense separation layer and the porous support layer comprise: a nano-graphite structure having an interplanar spacing of less than 3.6 Å; and a basal plane greater than 1.3 nm, and the dense separation layer comprises micropores having a radius greater than 4 Å.
2. The asymmetric hollow carbon fiber according to claim 1, wherein the fiber has a nano-crystalline graphite structure.
3. The asymmetric hollow carbon fiber according to any one of the preceding claims, wherein the fiber contains less than 50% pyrrole-based nitrogen by percentage of the total amount of nitrogen in the fiber.
4. The asymmetric hollow carbon fiber according to any one of the preceding claims, wherein the dense separation layer contains oxygen in an amount greater than 5 atomic% of the total atoms of the dense separation layer.
5. The asymmetric hollow carbon fiber according to any one of the preceding claims, wherein the dense separation layer contains oxygen in an amount less than 15 atomic% of the total atoms of the dense separation layer.
6. The asymmetric hollow carbon fiber according to any one of the preceding claims, wherein the fiber contains oxygen in an amount less than 5 atomic% of the total atoms of the fiber.
7. The asymmetric hollow carbon fiber according to any one of the preceding claims, wherein the fiber has a D(002) peak of less than 4.0 Å in transmission, as measured by X-ray scattering at an energy level of 17 keV.
8. A carbon molecular sieve membrane, the carbon molecular sieve membrane comprising, a plurality of asymmetric hollow carbon fibers according to any one of the preceding claims, and wherein the carbon molecular sieve membrane comprises channels formed between the dense separation layers of adjacent fibers.
9. The carbon molecular sieve membrane according to claim 8, wherein the carbon membrane does not include an external support.
10. A method for separating ethylene from a gas feed comprising ethylene and ethane, the method comprises: providing a carbon molecular sieve membrane according to claim 8 or 9; and passing the gas feed through the channels of the carbon molecular sieve membrane to produce a first stream having an increased concentration of ethylene and a second stream having an increased concentration of ethane.
11. A method for manufacturing the asymmetric hollow carbon fiber according to claims 1 to 7, wherein the method comprises: preparing a polymer precursor fiber; and pyrolyzing the polymer precursor fiber in a low-oxygen atmosphere at a temperature greater than 900 °C to form an asymmetric hollow carbon fiber.
12. The method according to claim 11, wherein the pyrolysis of the polymer precursor occurs in an atmosphere comprising an inert gas and oxygen.
13. The method according to claim 12, wherein the atmosphere contains less than 40 ppm of oxygen.
14. The method according to claim 12, wherein the atmosphere contains less than 10 ppm of oxygen.
15. The method according to any one of claims 11 to 14, wherein the polymer precursor is a polyimide.
Citation Information
Patent Citations
Energy conservation unit and system of a building by way of interactive learning
US20130030592A1
High carbon content filamentary membrane and method of making the same
US6565631B2
Method for producing carbon molecular sieve membranes in controlled atmospheres
US8709133B2